The Use of Lyricstraining.Com to Improve Students’ Listening Skills in Senior High School - Suweni, Dwi; Saefurrohman, Saefurrohman (Metafora: Jurnal Pembelajaran Bahasa Dan Sastra, 2024)
This research found out the impact of the use of lyricstraining.com on English language learning especially for listening skills. There were some benefits that both students and teachers got from the us of this app. The literature review was conducted to collect all the highlighted points from the available papers relating to the learning process. In advance, lyricstraining.com is an effective medium to help students reach their learning goals by using music. Therefore, it is worth applying in the classroom for listening activities. Later on, the researcher will observe it’s positive and negative then recommend the best way to use/apply lyricstraining.com in an English language classroom.